Pengaruh Makro Ekonomi dan Struktur Kepemilikan Terhadap Kinerja Keuangan dengan Pembiayaan sebagai Variabel Moderasi pada Sektor Perbankan Syariah di Indonesia Periode 2015-2019 - Khoirunnisa Khoirunnisa; Yunan Surono (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This research is to look at the macro-economic influence and ownership structure on financial performance with financing as a moderation variable in the Islamic banking sector in Indonesia in the period 2015 - 2019. This research uses the first independent variable, namely macro-economic variables consisting of inflation rate, central bank interest rate and rupiah exchange rate against US dollar. This study uses the second independent variable, namely the variable ownership structure of the company with indicators in the form of institutional ownership, foreign ownership and individual ownership and public ownership. Moderation variables are financing with indicators mudharabah financing, musyarakah financing and qardh financing. Dependent variable are financial performance with capital adequacy ratio (CAR), Non Performing Financing Gross (NPF Gross), Return On Asset (ROA), Financing to Deposit Ratio (FDR) and Rupiah Minimum Mandatory Giro (GWMR). The research sample used was sharia banking sector in Indonesia for 5 years observation period, starting from 2015 - 2019 recorded as 14 companies, which have complete financial statements and who have a complete research indicator report in the annual financial statements during the research period of 11 companies. This research is in the form of explanatory research and data analysis using Partial Least Square with Smart PLS 3.0 software. The results showed, Macro-economic variables have no effect on variable financial performance, variable ownership structure affects variable financial performance, variable financing is able to moderate the relationship between macro-economic variables and variable financial performance and has a negative direction (weakening) its influence on financial performance, variable financing is able to moderate the relationship between variable ownership structure and variable financial performance and has a positive direction (strengthening) its influence on financial performance.